Unhealthy Dieting During the COVID-19 Pandemic: An Opinion Regarding the Harmful Effects on Brain Health - Rentería, Iván; García-Suárez, Patricia Concepción; Moncada-Jiménez, José; Machado-Parra, Juan Pablo; Antunes, Barbara Moura; Lira, Fabio Santos [UNESP]; Jiménez-Maldonado, Alberto (Frontiers, 2022)
Since 2020, the world has been suffering from a pandemic that has affected thousands of people regardless of socio-economic conditions, forcing the population to adopt different strategies to prevent and control the advance of the disease, one of which is social distancing. Even though social distancing is a safe strategy to reduce the spread of COVID-19, it is also the cause of a rising sedentary behavior. This behavior develops an excess of fat tissue that leads to metabolic and inflammatory disruption related to chronic diseases and mental health disorders, such as anxiety, depression, and sleep issues. Furthermore, the adoption of dietary patterns involving the consumption of ultra-processed foods, higher in fats and sugars, and the reduction of fresh and healthy foods may play a role in the progress of the disease. In this perspective, we will discuss how an unhealthy diet can affect brain function and, consequently, be a risk factor for mental health diseases.
Keywords: brain; brain function; COVID-19 pandemic; mental health; nutrition